Parametric study on energy demands for steel special concentrically braced frames - Dogru, Selcuk; Aksar, Bora; Akbaş, Bülent; Shen, Jay (Techno-Press, 2017)
Structures are designed in such a way that they behave in a nonlinear manner when subject to strong ground motions. Energy concepts have been widely used to evaluate the structural performance for the last few decades. Energy based design can be expressed as the balance of energy input and the energy dissipation capacity of the structure. New research is needed for multi degree of freedom systems (MDOFs)-real structures-within the framework of the energy based design methodology. In this paper, energy parameters are evaluated for low-, medium- and high-rise steel special concentrically braced frames (SCBFs) in terms of total energy input and hysteretic energy. Nonlinear dynamic time history analyses are carried out to assess the variation of energy terms along the height of the frames. A seismic energy demand spectrum is developed and hysteretic energy distributions within the frames are presented.
Keywords: special concentrically braced frame; energy spectrum; energy demands; energy based design; energy dissipation